PSYCHOLOGICAL AND PEDAGOGICAL LAWS OF THE PROCESS OF MASTERING EDUCATIONAL MATERIALS (American Journal of Pedagogical and Educational Research, 2026)
This article extensively covers the psychological and pedagogical laws of the process of students' perception, understanding and assimilation of educational materials. The stages of the knowledge process, the role of will and attention in educational activities, and the deep cognitive mechanisms of the understanding process are analyzed. Also, the factors that ensure the intellectual development of students in the educational process are scientifically substantiated.